PENGARUH SEGMENTASI PASAR TERHADAP TINGKAT PENJUALAN PRODUK FASHION UMK: Studi Kasus Pada Pelaku UMK Bumi Orange Cinunuk Bandung - TIRIS SUDRARTONO (Coopetition : Jurnal Ilmiah Manajemen, 2019)
This study aimed to determine the Influence of Market Segmentation on Sales Micro Small Enterprises fashion Product Level Bumi Orange Cinunuk Bandung, background of this research is based on the Enterprises’s have not been maximal in selling their product even though there are big market opportunities in Bumi Orange Cinunuk Bandung. This study using a quantitative approach with the type of descriptive research. The analitycal methodology used simple linear regression, the analitycal test used was validity test, reliability test, normality test, correlation coefficient analysis, and hypothesis test. The tool used for testing this research is Statistical Product and Service Solution (SPSS) V. 20. The results,researchers suggest that products marketed to reach all market segments can be done by adjusting prices, product innovation and maximizing instant purchases by consumers so as to increaset sales Fashion product of Micro Small Enterprises’s Bumi Orange Cinunuk Bandung.